Archives for administrators or archives for antiquarians? A history of archive cataloguing in four oxford colleges - Riordan, M; Darwall-Smith, R (Routledge, 2009)
The history of archive cataloguing, particularly before the 20th century, has been much neglected. This paper offers a case study of archive cataloguing practices at four Oxford colleges from the 15th to the mid-20th century. The authors propose a model of changing attitudes towards recordkeeping that can be tested against archives elsewhere. Evidence from these colleges suggests that archive cataloguing practices varied widely at different times according to the needs of administrators and the wants of antiquarians.